PENGARUH PIJAT OKSITOSIN TERHADAP INVOLUSI UTERUS PADA IBU POST PARTUM DENGAN PERSALINAN LAMA DI RUMAH SAKIT WILAYAH KABUPATEN KLATEN - hamranani, Sri sat titi (MOTORIK Jurnal Ilmu Kesehatan (Journal of Health Science), 2011)
One of cause post partum bleeding is the uterine atonia. The aim of this research is to know the effect of rolling massage on uterus involution. Research design was prospective cohort. Sample was taken by consecutive sampling with 82 people in 3 hospital in Klaten region. Instrument is an observation sheet to evaluate the uterine involution in four times at first, second, third and tenth day post partum. The result show that was significant between rolling massage with uterine involution (p<0.05), with relative risk 5.250, 10.667, 4.125, and 2.857. The recommended of the research is Effect of paritas and the way of delivered on breastmilk production and uterus involution. Â  Key words : Rolling massage, uterus involution, prolonged labour.